Effects of Mycovirus Infections on Mycelial Growth and Fruiting Body Yield of the Edible Mushroom Lentinula edodes - Eunjin Kim; Mi-Jeong Park; Yeongseon Jang; Kang-Hyeon Ka (한국균학회지)
The shiitake mushroom, Lentinula edodes is an edible species cultivated worldwide. Various mycoviruses infecting L. edodes have been reported; however, research on the effects of viral infection remains limited. In this study, virus-cured strains were obtained using the mycelial fragmentation method from a wild-type strain NIFoS 51 infected with five different viruses, cultivated strain NIFoS 2778 (Sanbaekhyang) infected with two different viruses, and cultivated strain NIFoS 3435 (Sanhohyang) infected with one type of virus. The biological significance of viral infections was assessed by comparing isogenic virus-infected and viruscured strains. Viral infection was found to reduce mycelial growth rate and fruiting body yield. Traits of commercial importance, such as fruiting body fresh weight and pileus diameter, were affected by viral infections. This study suggests that preventing viral infections may be improve spawn quality management.